Management of Peptic Ulcer Bleeding in Different Case Volume Workplaces: Results of a Nationwide Inquiry in Hungary - István Rácz; Tibor Kárász; Krisztina Lukács; Ferenc Rácz; János Kersák; Judit Wacha; Tibor Szalóki; Magdolna Szász; István Gyenes; István Altorjay (Gastroenterology Research and Practice)
The aim of this study was to conduct a national survey to evaluate the recent endoscopic treatment and drug therapy of peptic ulcer bleeding (PUB) patients and to compare practices in high and low case volume Hungarian workplaces. A total of 62 gastroenterology units participated in the six-month study. A total of 3033 PUB cases and a mean of 8.15±3.9 PUB cases per month per unit were reported. In the 23 high case volume units (HCV), there was a mean of 12.9±5.4 PUB cases/month, whereas in the 39 low case volume units (LCV), a mean of 5.3±2.9 PUB cases/month were treated during the study period. In HCV units, endoscopic therapies for Forrest Ia, Ib, and IIa ulcers were significantly more often used than in LCV units (86% versus 68%; P=0.001). Among patients with stigmata of recent haemorrhage (Forrest I, II), bolus + continuous infusion PPI was given significantly more frequently in HCV than in LCV units (49.6% versus 33.2%; P=0.001). Mortality in HCV units was less than in LCV units (2.7% versus 4.3%; P=0.023). The penetration of evidence-based recommendations for PUB management is stronger in HCV units resulting lower mortality.